2022
DOI: 10.1093/oncolo/oyab006
|View full text |Cite
|
Sign up to set email alerts
|

Definitive Intensity-Modulated Chemoradiation for Anal Squamous Cell Carcinoma: Outcomes and Toxicity of 428 Patients Treated at a Single Institution

Abstract: Background Although intensity-modulated radiation therapy (IMRT) is considered the standard of care for the treatment of squamous cell carcinoma of the anus (SCCA), few large series have reported oncologic outcomes and toxicities. In this retrospective report, we aim to describe outcomes and toxicities after IMRT-based chemoradiation (CRT) for the treatment of SCCA, evaluate the impact of dose escalation (>54 Gy), and compare concurrent fluoropyrimidine in combination with either mitom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…These data suggest the importance of identifying strategies for better OARs preservation and late toxicities management. As several aspects of long-term function and quality of life (QoL) have been identified as factors to be investigated (e.g., sleep disorders) (34), anal cancer specific QoL questionnaires are being developed and validated and should be administered to patients over the course of follow-up visits (35)(36)(37). Unfortunately, our study lacks patient reported outcomes measures (PROMs), especially in terms of fecal continence; the opportunity to investigate this aspect, together with sexual function and sleep disorders is certainly interesting and challenging in the context of dose escalation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest the importance of identifying strategies for better OARs preservation and late toxicities management. As several aspects of long-term function and quality of life (QoL) have been identified as factors to be investigated (e.g., sleep disorders) (34), anal cancer specific QoL questionnaires are being developed and validated and should be administered to patients over the course of follow-up visits (35)(36)(37). Unfortunately, our study lacks patient reported outcomes measures (PROMs), especially in terms of fecal continence; the opportunity to investigate this aspect, together with sexual function and sleep disorders is certainly interesting and challenging in the context of dose escalation strategy.…”
Section: Discussionmentioning
confidence: 99%
“…158 For older patients or those who are unlikely to tolerate mitomycin, the optimal chemotherapy regimen remains uncertain. Some NCCN Panel members have used a combination of weekly cisplatin and daily 5-FU on days of RT 159 for chemoRT in localized anal cancer. Other potential strategies for this patient population may include capecitabine 1 RT or RT alone (without chemotherapy).…”
Section: Chemotherapymentioning
confidence: 99%
“…This treatment achieves high rates of local control and good overall survival outcomes with an estimated 5-year freedom from local failure of 81.2% and 5-year overall survival of 85.8%. 1 However, radiation to the pelvis can lead to significant acute and permanent side effects that impair patient quality of life (QOL). 2 , 3 , 4 …”
Section: Introductionmentioning
confidence: 99%